The Striking Level of Gender Inequality in the Nursing Profession: A Cross-sectional study among Nurses and Student Nurses from selected Hospitals and Nurses Training Institutions in the Northern Cities of Uganda. - Lalam, Lilly Grace; Nabushawo, Florence (Student’s Journal of Health Research Africa, 2022)
Background: The level of gender inequality in this study was established at 78.4% implying that out of 10(ten) nurses, at least 8(eight) have experienced unfair treatment because of their gender as a student or a staff. Both male and female nurses face gender disparity among patients/attendants, colleagues, other health professionals, their community, and even family members. Male nurses have remained the minority in the profession bringing a striking numerical gender inequality in the nursing profession. The objective of this study is to determine factors influencing Gender inequality in the Nursing Profession among nurses and student nurses from selected hospitals and nurses training institutions in the Northern Cities of Uganda. Methodology: A cross-sectional study design was used. Quantitative data were obtained from nurses and nursing students in selected study sites in Gulu, Lira, and Arua cities. The raw data was single -entered and analyzed using statistical software version 26 for analysis. Bivariate and univariate analysis methods were used to identify factors associated with gender inequality. Variables with a P-value of <0.05 with a 95% confidence interval were used to declare statistical significance. Results: 383 participants were interviewed. The level of gender inequality was established at 78.4%. Among the socio-demographic factors, gender (x 2=10.294, p-0.001), level of education attained (x 2=6.293, p-0.043), marital status (x 2=8.296, p-0.004) were significantly associated to gender inequality in the nursing profession. Conclusion: The prevalence of gender inequality in this study was 78.4%. Men remain the minority in the profession at 26.4%. Recommendations: The study recommends that quick comprehensive combined action is needed from government Ministries, nurses councils; NGOs, and international bodies fighting for gender equality to save the nursing profession from inequality. This action will contribute to the achievement of gender equality for all in all spheres of life.